Identifikasi, Penilaian, dan Pengendalian Risiko Kesehatan dan Keselamatan Kerja Pembuatan Tahu. - Teguh Irawan; Yulis Indriyani; Wafiq Zidna Amaliya; Rizqiani Karimah; Dyah Fauziah Fitriyani; Naila Salsabila; Haritsah Baihaqi; Tri Nugroho Kuncoro (Lontara Journal of Health Science and Technology, 2026)
Occupational Health and Safety (OHS) is an essential aspect in production processes, especially in Micro, Small, and Medium Enterprises (MSMEs) which are vulnerable to various workplace hazards. In tofu production industries, workers are often exposed to physical, chemical, mechanical, and ergonomic risks that can impact productivity and health. This study aims to analyze the types of occupational hazards and determine appropriate control measures using the HIRARC method. A qualitative descriptive approach was employed through a case study in one tofu-producing MSME in Batang Regency. Data collection methods included direct observation, semi-structured interviews with 15 workers, and documentation. Hazard identification, risk assessment, and risk control were conducted using the HIRARC method based on severity and likelihood. The study found multiple risks ranging from low to high levels, such as musculoskeletal disorders, burns, hearing loss, skin irritation, and respiratory issues. Proposed control strategies included the use of personal protective equipment (PPE), engineering controls such as ventilation and insulation, and administrative interventions. The findings indicate that the HIRARC method is effective for evaluating and managing OHS risks in MSMEs. This approach can support the implementation of a safer and healthier work environment in informal food production sectors.